Installation of Regulatory Sandbox Environment from the Perspective of the Brazilian Charter for Smart Cities - Lima, Camilla Matsuura de; Pasqualetto, Antonio (Revista Nacional de Gerenciamento de Cidades, 2023)
The development of smart and sustainable cities is becoming a real necessity for Brazilian municipalities. As such, the objective of this article was to present the concept of smart cities, as well as the guidelines proposed by the Brazilian Charter for Smart Cities. Subsequently, the Regulatory Sandbox in cities is presented. It is an instrument proposed in the Charter and regulated by Federal Complementary Law No. 182/2021, and can also be installed in Brazilian municipalities, through temporary Government authorization. Its institution aims to develop innovative business models and test new technologies, with a view not only to improving the quality of life of its population but also as an instrument to be used to actively participate in the construction of a smart city. In this way, the analysis of the scientific and academic production carried out about the Regulatory Sandbox in Brazil was decided upon. The methodology used was analytical research, through literature review. The results showed that digital transformation is a fundamental change in cities and, the institution of a Sandbox model is a secure way to test and validate resource-saving technologies.